Introduction pages, Nova Geodesia 3(2), 2023 - Paul SESTRAS (Nova Geodesia, 2023)
Nova Geodesia (https://novageodesia.ro), Issue 2, Volume 3, 2023: The papers published in this issue represent interesting novelties in different topics of geodetic science or related fields. Nova Geodesia publishes significant papers in geodesy and close topics related to cartography, engineering projects and construction, planetology, hydrography, geography, sociodemographic factors, urban planning, environmental administration, landscape, biodiversity, and ecology. Among the exciting articles, we invite readers to find news about: Assessing ethno-veterinary practices in Kashmir Himalayas: Traditional knowledge and its role in animal healthcare; Bryomonitoring of atmospheric elements in Sphagnum sp. commonly growing bryophyte in the Indian Himalayan region of Uttarakhand; GIS-remote sensing-based village-level hydrological balance approach for agricultural water planning.